Human fertility in India : social components and policy perspectives - Mandelbaum, David G. (Delhi, 1974)
The spectacular successes during the twentieth century in lowering mortality rates and in prolonging human life around the world have guaranteed mankind a continuing problem of too many births. This is not a serious difficulty everywhere, but it is a great handicap in some of the poorest and largest of nations. A good many governments have been trying in recent decades to do something about the heavy burdens caused by parents who are now too prolific. Although firm comparative assessments of the various national programs cannot yet be made, the record so far shows that certain of the smaller of the developing countries are meeting the figures for decreased fertility they have set for them selves that programs in the more populous developing nations have not yet succeeded in reducing fertility rates at the pace their respective plans proposed (Nortman 1972; Lapham and Mauldin 1972).
Keywords: Population Control India